(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2015)
The main focus of this paper lies in explaining the hypothesis that the exclusion of the (illegal) Bangladeshi immigrants in Assam has been the outcome of a continuous historical process undertaken by the political leaders of the state, rather than as a result of any particular mass uprising from ‘below’. This push from a top-down perspective changed the issue from one of economic consequences to a more religious nature, also culminating in a failed project to assert a unique indigenous ‘Assamese’ identity in relation to the ‘other’, all the while relegating the more usual aspects of open versus closed borders that figure in immigration discourses to the background.